COMBINATION OF ACUPUNCTURE THERAPY AND TURMERICLIQUORICE HERBS FOR CHRONIC COUGHING CASE - Purwanto, Intan Fahdelasari; Imandiri, Ario; Arifanti, Lusiana (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Coughing is a defense mechanism of the lung against several stimulants as well as to protecting the lung from any trauma. A long period of coughing about more than 8 weeks considered as Chronic coughing. Based on TCM, coughing is a manifestation of the lung which caused by an exogenous factor (such as cold wind and warm wind); and endogenous factor. It is classified as